The boy in the striped pajamas [videorecording (DVD)] - Herman, Mark; Farmiga, Vera; Thewlis, David, 1963-; Friend, Rupert (Miramax Home Entertainment : Walt Disney Studios Home Entertainment, 2009)
Poland, World War II. Innocent and naive 8-year-old Bruno is bored and restless in his new home. Ignoring his mother, he sets off on an adventure in the woods. He comes across a high fence which separates him from the people he can see through it. Soon he meets a young boy in striped pajamas, and a surprising friendship develops.